KURIKULUM PENDIDIKAN TERPADU MASA ISLAM KLASIK - Tihalimah Tihalimah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Knowledge developed in Islam has only one hierarchical goal, namely to Allah SWT. Arrangement of the concept of the educational curriculum, formulated and developed integrally, both aqliyah and naqliyah sciences which need integration so that the status of khalifatullah is truly realized. This research library research examines comprehensively the integrated education curriculum. The findings state that the final and integrated curriculum process will produce productive and creative students in the global struggle, especially in the field of education as well as having a good character.